Policy on Protection of Cultural Heritage through Communal Copyright in Supporting Sustainable Tourism - MAHENDRAWATI, Ni Luh Made (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
Tourism has become a prevalent discourse in Indonesia, considering that in the last few years, Tourism has become the highest contributor to the commodity revenue line. Paying close attention to the integration of tourism certainly involves multidiscipline in it so that efforts to develop tourism require integrated efforts from various parties as well as multidiscipline. It is essential to realize that the attractions of tourism in Indonesia can consist of everything that has a uniqueness, beauty, and value in the form of the diversity of natural, cultural, and human-made diversity. In real terms, it can be observed that cultural heritage is one of the valuable assets owned by a country (Indonesia) in supporting the development of tourism. Culture is a way of life that develops, is shared by a group of people, and is passed down from generation to generation. The culture referred to is the result of reason and reason, so that philosophy can be understood as originating from nothing, then thought by reason and ideas, then becoming. The process of creating a culture can logically be protected by Intellectual Property Rights (Copyright). During this time, the copyright-protected in Indonesia based on Law Number 28 of 2014 concerning Copyright is an Individual Right. It is understood that the copyright needed to protect cultural heritage is communal rights. How to regulate and apply copyright protection Communal communities will be studied more deeply so that there is a comprehensive and integrated model for protecting cultural heritage in Indonesia.